2006
DOI: 10.1051/0004-6361:20065986
|View full text |Cite
|
Sign up to set email alerts
|

Sausage oscillations of coronal loops

Abstract: Aims. Analytical theory predicts the existence of trapped global (or fundamental) sausage fast magnetoacoustic modes in thick and dense coronal loops only, with the periods estimated as the ratio of double the loop length and the Alfvén speed outside the loop. We extend this study to the leaking regime, considering global sausage modes of long loops with small density contrasts. Methods. Anti-symmetric fast magnetoacoustic perturbations (sausage, or m = 0 modes) of a low β plasma slab with the symmetric Epstei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
59
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 75 publications
(67 citation statements)
references
References 15 publications
8
59
0
Order By: Relevance
“…A further increase in L leads the sausage oscillations into the leaky regime, where P turns out to increase with L as well and shows saturation in the thin-tube limit (L/a 1). This behavior of sausage mode periods was analytically shown by Zaitsev & Stepanov (1975);Vasheghani Farahani et al (2014), and numerically demonstrated both via analysing the relevant dispersion diagrams (Kopylova et al 2007) and by solving the problem as an initial-boundary value one (Pascoe et al 2007a;Inglis et al 2009;Nakariakov et al 2012).…”
Section: Introductionsupporting
confidence: 52%
“…A further increase in L leads the sausage oscillations into the leaky regime, where P turns out to increase with L as well and shows saturation in the thin-tube limit (L/a 1). This behavior of sausage mode periods was analytically shown by Zaitsev & Stepanov (1975);Vasheghani Farahani et al (2014), and numerically demonstrated both via analysing the relevant dispersion diagrams (Kopylova et al 2007) and by solving the problem as an initial-boundary value one (Pascoe et al 2007a;Inglis et al 2009;Nakariakov et al 2012).…”
Section: Introductionsupporting
confidence: 52%
“…However, the excitation we choose is always sufficiently close to the eigenmode that the amplitude of these harmonics is very small with respect to the fundamental oscillation, and they are quickly damped. Thus, by running the simulation for sufficient time, the dominance of the desired mode is ensured (Pascoe et al 2007b).…”
Section: Numerical Modelmentioning
confidence: 99%
“…It is unclear whether or not a significant value of β 0 would have a strong effect on the period of the mode. As a first step therefore, we reproduce the result of Pascoe et al (2007b) showing the dependence of the period on the loop length L, but this time for a variety of β 0 values. This is achieved by simulating sausage oscillations in a loop with an Epstein density profile and a density contrast ratio of 10.…”
Section: The Period Of the Sausage Modementioning
confidence: 99%
See 2 more Smart Citations